TRANSPARANSI PENGELOLAAN DANA DESA DI DESA PASLATEN KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - BONALDY, SOETANDY; LENGKONG, FLORENCE DAICY; LONDA, VERY (Sam Ratulangi University, 2018)
Abstrack: Village funds used for village community empowerment are directed to the improvement orconstruction of village physical facilities and infrastructure that include the improvement of public facilities on asmall scale and environmental and road improvements, the roles of the village funding team and thestrengthening of village institutions and other village activities considered important . Certainly in this case mustinvolve the community from all the process because the purpose of the village funds to improve the villageeconomy. The main purpose of this research is to know the transparency of village fund management in PaslatenVillage Kauditan Subdistrict of North Minahasa Regency. In this research used qualitative research method, withprimary and secondary data source, with data collection technique, direct observation, interview anddocumentation study. In this study using data analysis in the form of data reduction, data presentation, dataverification or conclusion.The results obtained from this study are evident in the provision of village funds so far not done in a transparentmanner, this is evident from the various problems that arise such as access to documents that are still limited,lack of clarity of information about village funds provided by the government to the community, publicknowledge in legislation about the village fund is still minimal, so in reality the community cannot properlyguard the fund raising village. The main solution is the need for transparency from the village government to thecommunity about the village funding in detail by utilizing the electronic government system so that people caneasily access the village fund data, in addition the local government must work together with relevant parties inproviding socialization to the community and the village government about rules governing village funds,transparency of village funds and information disclosure to the community about village funds.Keywords: Transparency, Village funds